On extreme Gibbs measures of the Vannimenus model - Ganikhodjaev, Nasir; Akin, Hasan; Uguz, Selman; Temir, Seyit (Institute of Physics Publishing Ltd., 2011)
One of the main problems of statistical physics is that of describing all Gibbs measures corresponding to a given Hamiltonian. It is well known that such measures form a nonempty convex compact subset in the set of all probability measures. The purpose of this paper is to investigate extreme Gibbs measures of the Vannimenus model.